Anaerobic co-cultivation of multi-algal species with oil palm empty fruit bunches for mill effluent treatment and biomethane production - Ahmad, A. (Penerbit UTM Press, 2016)
This study investigated the optimization of anaerobic co-cultivation of multi-algal species with Oil Palm Empty Fruit Bunches (OPEFB) for Palm Oil Mill Effluent (POME) treatment and biomethane production. The highest removal of COD (95-98), BOD (90-98), TOC (81-86) and TN (78-80) were achieved after 7 days anaerobic treatment with the presence of microalgae. The highest biomethane (4,651.9 mL CH4/L POME/day) and the specific biogas production rate (0.124 m3/kg COD/day) with CO2 (2,265.9mL CO2/L POME/day) were achieved by co-cultivating N. oculata and Chlorella sp. (each at 1 mL/mL POME) with OPEFB (0.12 g/mL POME). The combination of N. oculata (2 mL/mL POME) with T. suecica or Chlorella sp. (each at 1 mL/mL POME), and OPEFB (0.12 g/mL POME) obtained high biomethane (4,018.9 mL CH4/L POME /day) but lower biogas (0.097 m3/kg COD/day) and CO2 (2,079.5mL CO2/L POME/day). Generally, low OPEFB and having all the three strains or increasing the level of any (2 mL/mL POME) especially T. suecica, could lower biomethane (870-953 mL CH4/L POME/day) and CO2 (803-854mL CO2/L POME/day), with the biogas around 0.08-0.09 m3/kg COD/day. The optimum conditions were predicted by Response Surface Methodology and the multiple coefficients of determination, r2, of 86 suggests good agreement between experimental and predicted values. Â© 2016 Penerbit UTM Press. All rights reserved.